KEJADIAN INFEKSI NEMATODA USUS DAN HUBUNGANNYA DENGAN PHBS DAN STATUS GIZI PADA PENDUDUK YANG TINGGAL DI DAERAH TEMPAT PEMBUANGAN AKHIR SAMPAH - Nurmila Sunati; Kevin Pascoal; Ketrina Konoralma; Jasman Jasman; Indra Elisabet Lalangpuling (LPPM Universitas Abdurrab, 2023)
Landfill (TPA) is a place to dispose of waste and waste to minimize the impact of waste on human health and the environment. People who live around the landfill are at risk of experiencing health problems. The main factor in transmitting STH worm eggs to the human body is poor hygiene. Cleanliness in question is personal hygiene, cleanliness of the food consumed and also the cleanliness of the environment where you live and work. The most common cause of this class of worms is Soil Transmitted Helminths (STH), which are intestinal worms that are transmitted through the soil. This study aims to see incident of nematode infectioan and the relationship between helminthiasis infection with nutritional status and personal hygiene behaviours. It was an observational study with cross-sectional design. This type of research is an observational study with a cross-sectional design. The sample are 93 responden at Sumompo Landfill were taking by purposive sampling. The results found that 24,8% respondent had worm infections with Ascaris lumbricoide,Strongyloises stercoralys and Anchylostoma duodenale. The results of statistical tests on the relationship between worm infection with healthy living behavior and nutritional status showed p>0.05. The conclusion are 25.8% respondents had worm infection; and there is no significant relationship between worm infection with clean and healthy living behavior, and nutritional status.